Characteristic mutations induced in the small intestine of Msh2-knockout gpt delta mice - Yasunobu Aoki; Mizuki Ohno; Michiyo Matsumoto; Michi Matsumoto; Kenichi Masumura; Takehiko Nohmi; Teruhisa Tsuzuki (Genes and Environment, 2021)
Abstract Background Base pair mismatches in genomic DNA can result in mutagenesis, and consequently in tumorigenesis. To investigate how mismatch repair deficiency increases mutagenicity under oxidative stress, we examined the type and frequency of mutations arising in the mucosa of the small intestine of mice carrying a reporter gene encoding guanine phosphoribosyltransferase (gpt) and in which the Msh2 gene, which encodes a component of the mismatch repair system, was either intact (Msh2+/+::gpt/0; Msh2-bearing) or homozygously knockout (KO) (Msh2−/−::gpt/0; Msh2-KO). Results Gpt mutant frequency in the small intestine of Msh2-KO mice was about 10 times that in Msh2-bearing mice. Mutant frequency in the Msh2-KO mice was not further enhanced by administration of potassium bromate, an oxidative stress inducer, in the drinking water at a dose of 1.5 g/L for 28 days. Mutation analysis showed that the characteristic mutation in the small intestine of the Msh2-KO mice was G-to-A transition, irrespective of whether potassium bromate was administered. Furthermore, administration of potassium bromate induced mutations at specific sites in gpt in the Msh2-KO mice: G-to-A transition was frequently induced at two known sites of spontaneous mutation (nucleotides 110 and 115, CpG sites) and at nucleotides 92 and 113 (3′-side of 5′-GpG-3′), and these sites were confirmed to be mutation hotspots in potassium bromate-administered Msh2-KO mice. Administration of potassium bromate also induced characteristic mutations, mainly single-base deletion and insertion of an adenine residue, in sequences of three to five adenine nucleotides (A-runs) in Msh2-KO mice, and elevated the overall proportion of single-base deletions plus insertions in Msh2-KO mice. Conclusions Our previous study revealed that administration of potassium bromate enhanced tumorigenesis in the small intestine of Msh2-KO mice and induced G-to-A transition in the Ctnnb1 gene. Based on our present and previous observations, we propose that oxidative stress under conditions of mismatch repair deficiency accelerates the induction of single-adenine deletions at specific sites in oncogenes, which enhances tumorigenesis in a synergistic manner with G-to-A transition in other oncogenes (e.g., Ctnnb1).